Constitutionalism justified Rainer Forst in discourse - Herlin-Karnell, Ester; Klatt, Matthias; Morales Zúñiga, Hector A. (Oxford University Press, 2019)
Rainer Forst is a leading German political philosopher and was named "the most important political philosopher of his generation" upon his 2012 receipt of the Leibniz Prize. This book brings together discussion from political philosophy, constitutional theory, and legal philosophy to examine Forst's theory of justice, paying special attention to the application of his moral theory to legal fields. Forst then responds to his interlocutors in a concluding chapter. The book is structured from the general to the specific, and begins by examining Forst's "right to justification" as the basis for justice. This right is in the second section extended to the realm of constitutional theory. The third section addresses justification and proportionality within constitutional law. The concluding section sees Forst respond to the foregoing chapters"--